Comparative efficacy of uterine artery embolization versus laparoscopic myomectomy in treating uterine fibroids: a propensity score matched analysis - Cunbao Wei; Xingwei Sun; Shenzhi Li; Xuming Bai; Yong Jin (Discover Oncology)
Abstract Objective The aim of this study was to comparatively analyze the therapeutic effects of uterine artery embolization (UAE) and laparoscopic myomectomy (LM) on uterine fibroids to determine which treatment method is more beneficial for patients. Materials and methods A retrospective study was conducted on 396 patients who underwent UAE (n = 153) or LM (n = 243) treatment from April 2010 to September 2019. After 1:1 propensity score matching (PSM), a comparative analysis was conducted on surgical trauma magnitude, postoperative recovery time, improvement in associated symptoms and quality of life, surgical adverse events, recurrence rates, and further interventions. Results In PSM, 66 pairs (132 patients) were successfully matched. Both treatments significantly alleviated symptoms and enhanced quality of life. Compared to the LM group, the UAE group had less intraoperative bleeding (P < 0.001), a lower rate of hemoglobin decrease (P < 0.001), shorter operation, postoperative, and overall hospital stays (P < 0.001), and a lower postoperative recurrence rate (P < 0.05), all statistically significant. Moreover, the UAE group showed notable advantages in postoperative activities (P < 0.05). However, UAE patients faced higher hospitalization costs (P < 0.001). Adverse event rates (7.6% vs. 9.1%) and postoperative reintervention rates (7.6% vs. 7.6%) were relatively low and not significantly different between groups (P > 0.05). Conclusion Both UAE and LM can significantly improve patient symptoms and enhance their quality of life, and both treatment methods have low rates of adverse events and reinterventions. Compared to LM, UAE treatment for uterine fibroids presents advantages such as less trauma, faster recovery, and lower recurrence rate, but has higher treatment costs.